(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The success and failure of any business in general and startups in particular largely depend on coping with challenges that emerged like the commercialization of novel technique or technology prepositions into viable revenue-generating products or services. Besides this financing, the startups were also troublesome to the investors due to a lack of adequate return for a longer period of time with the aggregated risk involved in it. The young graduates from various universities are entering into the startup business without understanding the ecosystem. The aim of this work is to analyse the challenges encountered by the startups , their awareness levels on various policies of the Government and the role played by the startup entrepreneurs in the startup ecosystem.